Preparation method of iron-silicon magnetic powder core with low magnetic conductivity and high strength
By generating a phosphorus film on the surface of iron-silicon alloy magnetic powder and coating it with magnesium aluminum silicate gel, combined with low-temperature preheating and high-temperature heat treatment, the problem of insufficient strength of traditional soft magnetic materials at high temperatures is solved, and the stable application of magnetic powder cores in high-temperature environments is realized.
Patent Information
- Application Number
- CN202511327194.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-17
- Publication Date
- 2026-01-06
AI Technical Summary
Traditional soft magnetic materials are difficult to maintain high strength in high-temperature environments, which makes the magnetic powder cores prone to breakage or damage under high-temperature conditions, limiting their widespread application.
Phosphating is used to generate a phosphorus film on the surface of iron-silicon alloy magnetic powder, which is then coated with magnesium aluminum silicate gel. Combined with low-temperature preheating and high-temperature heat treatment, a dense protective film and an inorganic glass binder phase are formed, which improves the mechanical strength of the magnetic powder core.
Without reducing magnetic properties, the strength of the magnetic powder core is significantly improved, enabling it to remain stable at high temperatures for extended periods and adapt to harsh working environments.
Smart Images

Figure CN121281988A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of soft magnetic materials technology, and more specifically, to a method for preparing a low-permeability, high-strength iron-silicon magnetic powder core. Background Technology
[0002] With the rapid development of modern electronic technology, the demand for soft magnetic materials is increasing, requiring these materials to possess superior performance. As an important soft magnetic material, metal powder cores are widely used in voltage converters, inductors, and other fields due to their low power loss (Pcv) and stable performance over a wide temperature range. For applications involving high frequency, high current, high power density, and harsh operating environments, low-permeability, high-strength metal powder cores are required. However, preparing low-permeability metal powder cores requires adding a large amount of non-magnetic insulating material and then performing low-pressure molding. This leads to a sharp decrease in the strength of the powder core, making it difficult to withstand long-distance transportation, winding processing, and subsequent high-strength or special conditions (such as high temperatures). This makes them prone to breakage and damage, limiting the widespread application of magnetic powder cores.
[0003] Currently, there is limited research on improving the strength of magnetic powder cores. Industrially, organic resin impregnation is commonly used. This involves immersing the heat-treated magnetic powder core in molten organic resin under vacuum, followed by resin cooling and solidification, thereby increasing the core's strength. However, high-strength magnetic powder cores prepared by organic resin impregnation are difficult to operate for extended periods at high temperatures (200°C). At high temperatures, the resin ages and decomposes, leading to a decrease in the core's strength. Summary of the Invention
[0004] This application provides a method for preparing a low-permeability, high-strength iron-silicon magnetic powder core, which solves the technical problem that traditional soft magnetic materials cannot maintain high strength under high-temperature conditions.
[0005] A method for preparing a low-permeability, high-strength iron-silicon magnetic powder core includes the following steps: Step 1: After phosphating the iron-silicon alloy magnetic powder, the phosphated magnetic powder is then physically coated with a layered magnesium aluminum silicate gel. Step 2: Preheat the magnetic powder obtained in Step 1 in an inert atmosphere; Step 3: Thoroughly mix the magnesium aluminum silicate gel, binder and magnetic powder obtained in step 2, heat the mixture and mechanically stir until the powder is dry; Step 4: Mechanically stir the magnetic powder obtained in Step 3 with the lubricant until they are evenly mixed, and then press them into a magnetic powder core blank. Step 5: Heat treat the blank obtained in step 4 under an inert protective atmosphere.
[0006] Preferably, the mass fractions of each component in the phosphating solution used in the phosphating treatment are as follows: 5-15 parts of phosphoric acid 10-60 parts of potassium dihydrogen phosphate 0-20 parts of potassium hydrogen phosphate Potassium dichromate 20-60 parts.
[0007] For example, the mass fractions of each component of the phosphating solution used in the phosphating treatment are as follows: 10 parts phosphoric acid 50 parts of potassium dihydrogen phosphate 20 parts of potassium hydrogen phosphate 20 parts of potassium dichromate For example, the mass fractions of each component of the phosphating solution used in the phosphating treatment are as follows: 15 parts of phosphoric acid 30 parts of potassium dihydrogen phosphate 5 parts potassium hydrogen phosphate 50 parts of potassium dichromate Preferably, in step 1, the phosphating solution used in the phosphating treatment is 0.5%-1.0% of the mass of the iron-silicon alloy magnetic powder, such as 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, or 1.0%.
[0008] Preferably, in step 1, the amount of magnesium aluminum silicate gel added is 0.4%-1.2% of the mass of the magnesium aluminum silicate dry powder as alloy magnetic powder, such as 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, or 1.2%.
[0009] Preferably, in step 2, the preheating temperature of the preheating treatment is 600 ℃~750 ℃, such as 600 ℃, 650 ℃, 700 ℃, 750 ℃.
[0010] Preferably, the preheating treatment time is 0.5h to 1.5h, such as 0.5h, 0.8h, 1h, 1.2h, or 1.5h.
[0011] Preferably, in step 3, the adhesive is water glass.
[0012] Preferably, in step 3, the amount of water glass added is such that the liquid mass of water glass accounts for 0.8%-2.0% of the mass of alloy magnetic powder, such as 0.8%, 1.0%, 1.2%, 1.5%, 1.8%, 2.0%.
[0013] Preferably, in step 3, the amount of magnesium aluminum silicate gel added is 0.5%-1.5% of the mass of the magnesium aluminum silicate dry powder as alloy magnetic powder, such as 0.5%, 0.6%, 0.8%, 1.0%, 1.2%, or 1.5%.
[0014] Preferably, in step 4, the molding pressure is 900MPa-1200MPa, such as 900MPa, 950MPa, 980MPa, 1000MPa, or 1200MPa.
[0015] Preferably, in step 5, the heat treatment temperature is 750℃-850℃, such as 750℃, 780℃, 800℃, 820℃, or 850℃.
[0016] Preferably, the heat treatment time is 0.5h-1.5h, such as 0.5h, 0.8h, 1.0h, 1.2h, or 1.5h.
[0017] Beneficial effects: This invention proposes a method for preparing a low-permeability, high-strength iron-silicon magnetic powder core. A phosphating solution composed of phosphoric acid, potassium dihydrogen phosphate, potassium hydrogen phosphate, and potassium dichromate is added to the iron-silicon magnetic powder. The acidic potassium phosphate salt reacts chemically with the iron-silicon to form a phosphorus film on the magnetic powder surface. The dichromate ions in the potassium dichromate undergo a redox reaction with the metal surface, forming a dense protective film that isolates the metal from corrosive media, thus inhibiting corrosion and preventing the iron-silicon from rusting. Simultaneously, the potassium dichromate also ensures the potassium content.
[0018] The surface of the phosphated magnetic powder is coated with a layer of magnesium aluminum silicate. Through low-temperature preheating treatment, the surface coating is made tight and not easy to fall off, thus ensuring that the magnetic properties do not deteriorate, and also ensuring the low permeability of the magnetic powder core.
[0019] By adjusting the ratio of aluminum, potassium, and silicon to achieve a K2O mass fraction of 25-35 wt%, a SiO2 mass fraction of 60-70 wt%, and an Al2O3 mass fraction of 5-15 wt%, a eutectic phenomenon was generated at 700 ℃-800 ℃ according to the Al2O3-SiO2-K2O ternary phase diagram. As a result, the coating layer on the surface of the magnetic powder underwent partial liquid phase sintering, which greatly improved the fracture stress of the magnetic powder core, achieving a fracture stress ≥500 N.
[0020] Therefore, this invention uses an inorganic coating agent to undergo liquid-phase sintering at the heat treatment temperature of the magnetic powder core, which significantly improves the strength of the magnetic powder core without reducing its magnetic properties, and ensures that its strength does not decrease during long-term use at high temperatures. Attached Figure Description
[0021] The accompanying drawings, which form part of this application, are used to provide a further understanding of this application. The illustrative embodiments and descriptions of this application are used to explain this application and do not constitute an undue limitation of this application. In the drawings: Figure 1 This is a cross-sectional microstructure of the low-permeability, high-strength iron-silicon magnetic powder core prepared according to an embodiment of the present invention. Detailed Implementation
[0022] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. This application will now be described in detail with reference to the accompanying drawings and embodiments.
[0023] An embodiment of the present invention provides a method for preparing a low-permeability, high-strength iron-silicon magnetic powder core, comprising the following steps: Step 1: After phosphating the iron-silicon alloy magnetic powder, the phosphated magnetic powder is then physically coated with a layered magnesium aluminum silicate gel.
[0024] Step 2: Preheat the magnetic powder obtained in Step 1 in an inert atmosphere.
[0025] Step 3: Thoroughly mix the magnesium aluminum silicate gel, binder and magnetic powder obtained in step 2, heat the mixture and mechanically stir until the powder is dry.
[0026] Step 4: Mechanically stir the magnetic powder obtained in Step 3 with the lubricant until they are evenly mixed, and then press them into a magnetic powder core blank.
[0027] Step 5: Heat treat the blank obtained in step 4 under an inert protective atmosphere.
[0028] In the above method, step 1 generates a dense and strongly adherent Fe-PO substrate layer through phosphating, and constructs a preliminary, well-covering physical insulation barrier using magnesium aluminum silicate gel. Step 2 involves low-temperature preheating under an inert atmosphere to dehydrate and stabilize the composite insulation layer formed in step 1, preventing it from falling off and laying a solid foundation for subsequent processes. This step is crucial for ensuring low loss. In step 3, the added magnesium aluminum silicate gel and Al-K-Si compound are mixed with the binder and provide preliminary molding strength under heating. In step 4, magnetic powder and lubricant are mixed and pressed to obtain a high-density blank. In the final heat treatment process, the temperature is high, the binder is decomposed, and the Al-K-Si compound system undergoes liquid-phase sintering to form a robust inorganic glass binder phase, achieving extremely high mechanical strength (≥500N).
[0029] like Figure 1 The figure shows the cross-sectional microstructure of the low permeability high strength iron-silicon magnetic powder core prepared in this embodiment. As can be seen from the figure, the magnetic powder surface coating and binder partially form a liquid state at high temperature, that is, a low eutectic phenomenon is formed.
[0030] In this embodiment, the ternary structure formed by liquid-phase sintering comprises P and K from the phosphating substrate, and magnesium aluminum silicate added twice. The liquid phase comes from the gel and binder. These components achieve their respective physical coating effects in their respective steps. Under appropriate proportions, they eutectic on the surface of the magnetic powder during heat treatment, achieving liquid-phase sintering and thus improving strength. Therefore, in order to obtain an appropriate proportion while ensuring the coating function, the content ratio of each component is quite important in this embodiment.
[0031] In some preferred embodiments, the mass fractions of the components of the phosphating solution used in the phosphating treatment are as follows: 5-15 parts of phosphoric acid 10-60 parts of potassium dihydrogen phosphate 0-20 parts of potassium hydrogen phosphate Potassium dichromate 20-60 parts.
[0032] In some preferred embodiments, in step 1, the phosphating solution used in the phosphating treatment is 0.5%-1.0% of the mass of the iron-silicon alloy magnetic powder.
[0033] In some preferred embodiments, in step 1, the amount of magnesium aluminum silicate gel added is 0.4%-1.2% of the mass of the alloy magnetic powder.
[0034] In some preferred embodiments, in step 2, the preheating temperature of the preheating treatment is 600 ℃~750 ℃.
[0035] In some preferred embodiments, in step 2, the preheating treatment time is 0.5 h to 1.5 h.
[0036] In some preferred embodiments, in step 3, the adhesive is water glass and magnesium aluminum silicate gel.
[0037] In some preferred embodiments, in step 3, the amount of water glass added is such that the liquid mass of water glass accounts for 0.8%-2.0% of the mass of the alloy magnetic powder.
[0038] In some preferred embodiments, in step 3, the amount of magnesium aluminum silicate gel added is 0.5%-1.5% of the mass of the magnesium aluminum silicate dry powder as alloy magnetic powder.
[0039] In some preferred embodiments, in step 4, the molding pressure is 900MPa-1200MPa.
[0040] In some preferred embodiments, in step 5, the heat treatment temperature is 750℃-850℃.
[0041] In some preferred embodiments, the heat treatment time in step 5 is 0.5h-1.5h.
[0042] The applicant prepared three magnetic powder core samples based on the method in the above embodiments. In addition, two magnetic powder core samples were prepared as comparative examples by impregnation and curing with organic resin. All magnetic powder cores were of the same size, i.e., they were ring-shaped with an outer diameter D = 26.92 mm, an inner diameter d = 14.73 mm, and a height of 11.1 mm.
[0043] Example 1
[0044] Gas-atomized iron-silicon alloy magnetic powder with a particle size of <74 μm was used as raw material. The alloy magnetic powder was mixed with 0.7 wt% of a phosphating solution. The mass fractions of each component in the phosphating solution are as follows: 10 parts phosphoric acid 50 parts of potassium dihydrogen phosphate 20 parts of potassium hydrogen phosphate 20 parts of potassium dichromate Phosphating solution and alloy magnetic powder are mixed and mechanically stirred until dry. Then, it is mixed with magnesium aluminum silicate sol, which accounts for 1.0 wt% of the alloy magnetic powder mass, and stirred and dried. The magnesium aluminum silicate sol accounts for 20% of the mass of magnesium aluminum silicate dry powder. The phosphated and physically coated magnetic powder is preheated at 650 °C in a N2 protective atmosphere for 1 h. The magnesium aluminum silicate sol, which accounts for 1.0 wt% of the alloy magnetic powder mass, is mixed with 1.5 wt% of the liquid mass of the alloy magnetic powder water glass. This mixture is then mixed with the preheated magnetic powder, stirred and dried. Zinc stearate, which accounts for 0.3 wt% of the alloy magnetic powder mass, is added and mixed evenly. The mixture is pressed into a blank under a pressure of 980 MPa. Finally, it is heat-treated at 800 °C in a N2 protective atmosphere for 1 h to prepare a magnetic powder core sample.
[0045] Example 2
[0046] Gas-atomized iron-silicon alloy magnetic powder with a particle size of <74 μm was used as raw material. The alloy magnetic powder was mixed with 1.0 wt% of a phosphating solution. The mass fractions of each component in the phosphating solution are as follows: 5 parts phosphoric acid 60 parts of potassium dihydrogen phosphate 20 parts of potassium hydrogen phosphate 25 parts of potassium dichromate Phosphating solution and alloy magnetic powder are mixed and mechanically stirred until dry. Then, it is mixed with magnesium aluminum silicate sol, which contains 1.2 wt% magnesium aluminum silicate dry powder as alloy magnetic powder, and stirred and dried. The magnesium aluminum silicate sol contains 20% magnesium aluminum silicate dry powder as alloy magnetic powder. The phosphated and physically coated magnetic powder is preheated at 700 °C in a N2 protective atmosphere for 1 h. Magnesium aluminum silicate sol, which contains 0.8 wt% magnesium aluminum silicate dry powder as alloy magnetic powder, is mixed with 1.0 wt% liquid water glass as alloy magnetic powder, and then mixed with the preheated magnetic powder. The mixture is stirred and dried. Zinc stearate, which contains 0.3 wt% zinc stearate as alloy magnetic powder, is added and mixed evenly. The mixture is pressed into a blank under a pressure of 1000 MPa and finally heat-treated at 820 °C in a N2 protective atmosphere for 0.8 h to prepare a magnetic powder core sample.
[0047] Example 3
[0048] Gas-atomized iron-silicon alloy magnetic powder with a particle size of <74 μm was used as raw material. The alloy magnetic powder was mixed with a phosphating solution accounting for 0.5 wt% of the alloy magnetic powder mass. The mass proportions of each component in the phosphating solution are as follows: 15 parts of phosphoric acid 30 parts of potassium dihydrogen phosphate 5 parts potassium hydrogen phosphate 50 parts of potassium dichromate Phosphating solution and alloy magnetic powder are mixed and mechanically stirred until dry. Then, it is mixed with magnesium aluminum silicate sol (0.8 wt% of the alloy magnetic powder mass), stirred and dried. The magnesium aluminum silicate sol contains 20% magnesium aluminum silicate dry powder. The phosphated and physically coated magnetic powder is preheated at 600 °C in a N2 protective atmosphere for 1.5 h. Magnesium aluminum silicate sol (0.6 wt% of the alloy magnetic powder mass of magnesium aluminum silicate dry powder) and water glass (2.0 wt% of the alloy magnetic powder mass of liquid) are mixed and then mixed with the preheated magnetic powder. The mixture is stirred and dried, and zinc stearate (0.3 wt% of the alloy magnetic powder mass) is added and mixed evenly. The mixture is pressed into a blank under a pressure of 950 MPa and finally heat-treated at 780 °C in a N2 protective atmosphere for 1.2 h to prepare a magnetic powder core sample.
[0049] Comparative Example 1 Gas-atomized iron-silicon alloy magnetic powder with a particle size of <74 μm was used as raw material. The alloy magnetic powder was mixed with 0.7 wt% of a phosphating solution. The mass fractions of each component in the phosphating solution are as follows: 10 parts phosphoric acid 50 parts of potassium dihydrogen phosphate 20 parts of potassium hydrogen phosphate 20 parts of potassium dichromate Phosphating solution is mixed with iron-silicon alloy magnetic powder and mechanically stirred until dry. Then, it is mixed with magnesium aluminum silicate sol, which accounts for 1.0% of the mass of the alloy magnetic powder, and stirred and dried. The magnesium aluminum silicate sol accounts for 20% of the mass of the magnesium aluminum silicate. The magnesium aluminum silicate sol, which accounts for 1.0 wt% of the mass of the alloy magnetic powder, is mixed with 1.5 wt% of the liquid mass of the alloy magnetic powder, and then mixed with the phosphated and physically coated magnetic powder. The mixture is stirred and dried, and 0.3 wt% of the mass of zinc stearate is added and mixed evenly. The mixture is pressed into a blank under a pressure of 980 MPa, and finally heat-treated at 800℃ in a N2 protective atmosphere for 1 hour to prepare a magnetic powder core sample.
[0050] Compared to Example 1, this comparative example only lacks the preheating process following phosphating and physical coating.
[0051] Comparative Example 2: Gas-atomized iron-silicon alloy magnetic powder with a particle size of <74 μm was used as raw material. The magnetic powder was mixed with a phosphating solution accounting for 0.7 wt% of the alloy magnetic powder mass. The mass proportions of each component in the phosphating solution are as follows: 10 parts phosphoric acid 50 parts of potassium dihydrogen phosphate 20 parts of potassium hydrogen phosphate 20 parts of potassium dichromate Phosphating solution and iron-silicon alloy magnetic powder are mixed and mechanically stirred until dry. Then, it is mixed with magnesium aluminum silicate sol (1.0% by weight of alloy magnetic powder), stirred and dried. The magnesium aluminum silicate sol contains 20% magnesium aluminum silicate dry powder. 0.3 wt% zinc stearate and 0.8 wt% silicone resin binder (by weight of alloy magnetic powder) are added and mixed evenly. The mixture is pressed into a blank under a pressure of 950 MPa. Finally, it is heat-treated at 780℃ in a N2 protective atmosphere for 1 hour to prepare a magnetic powder core sample. The sample is then vacuum impregnated with epoxy resin and washed with acetone to remove the epoxy resin from the surface of the magnetic ring, resulting in the impregnated sample.
[0052] Compared with Example 1, this comparative example only underwent phosphating and physical coating, without the preheating treatment and subsequent processes in the method of the present invention. Instead, the phosphating and physical coated powder was directly pressed under the action of lubricant and binder, and then cured by epoxy resin impregnation after heat treatment.
[0053] The inductance L and DC superposition performance (%μe) of the prepared iron-silicon magnetic powder core were measured by winding 20 turns of enameled copper wire with a diameter of Φ=0.8 mm, and the power loss was measured by winding 20 turns of double-stranded wire. The soft magnetic properties of Examples 1-3 and Comparative Examples 1-2 are shown in Table 1: Table 1
[0054] From Table 1, we can obtain: (1) The low permeability and high strength iron-silicon magnetic powder cores prepared by the method of the present invention have lower effective permeability than comparative examples 1-2 in Examples 1-3, and the strength of the samples after heat treatment is much higher than that of comparative examples 1-2. Although comparative example 2 improves its strength by epoxy resin impregnation, its strength drops to the strength before impregnation under the conditions of 200℃ and 1000h.
[0055] (2) In Comparative Examples 1 and 2, the magnetic properties of the phosphating physically coated magnetic powder were not preheated, which led to a sharp increase in its permeability, high power loss, and a sharp decrease in the strength of the magnetic powder core.
[0056] The above are merely embodiments of this application and are not intended to limit the scope of this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the scope of the claims of this application.
Claims
1. A method for producing a low permeability high strength iron-silicon magnetic powder core, characterized by, It comprises the following steps: Step 1, after phosphating treatment of iron-silicon alloy magnetic powder, the phosphated magnetic powder is physically coated with magnesium aluminum silicate gel with layered structure; Step 2, the magnetic powder obtained in step 1 is preheated in an inert atmosphere; Step 3, the magnesium aluminum silicate gel, the binder and the magnetic powder obtained in step 2 are mixed uniformly, the mixed system is heated and mechanically stirred until the powder is dry; Step 4, the magnetic powder obtained in step 3 is mixed uniformly with a lubricant and then pressed into a magnetic powder core blank; Step 5, the blank obtained in step 4 is heat treated in an inert protective atmosphere.
2. The method of claim 1, wherein, The mass fractions of the components of the phosphating solution used in the phosphating treatment are as follows: Phosphoric acid 5-15 parts Potassium dihydrogen phosphate 10-60 parts Potassium hydrogen phosphate 0-20 parts Potassium dichromate 20-60 parts.
3. The preparation method according to claim 1, characterized in that, In step 1, the phosphating solution used in the phosphating treatment is 0.5%-1.0% of the mass of the iron-silicon alloy magnetic powder.
4. The preparation method according to claim 1, characterized in that, In step 1, the amount of magnesium aluminum silicate gel added is 0.4%-1.2% of the mass of the alloy magnetic powder.
5. The method of claim 1, wherein the step of forming the first and second layers is performed by a process selected from the group consisting of: sputtering, evaporation, and chemical vapor deposition. In step 2, the preheating temperature of the preheating treatment is 600℃-750℃. Preferably, the preheating treatment time is 0.5h-1.5h.
6. The method of claim 1, wherein the step of forming the first and second layers is performed by a process selected from the group consisting of: sputtering, evaporation, and chemical vapor deposition. In step 3, the binder is water glass.
7. The preparation method according to claim 6, characterized in that, In step 3, the amount of water glass added is 0.8%-2.0% of the mass of the water glass in liquid state to the mass of the alloy magnetic powder.
8. The preparation method according to claim 6, characterized in that, In step 3, the amount of magnesium aluminum silicate gel added is 0.5%-1.5% of the mass of the aluminum magnesium silicate dry powder to the mass of the alloy magnetic powder.
9. The method of claim 1, wherein the step of forming the first and second layers is performed by a process selected from the group consisting of: sputtering, evaporation, and chemical vapor deposition. In step 4, the forming pressure is 900MPa-1200MPa.
10. The method of claim 1, wherein the step of forming the first and second layers is performed by a process selected from the group consisting of: sputtering, evaporation, and chemical vapor deposition. In step 5, the heat treatment temperature is 750℃-850℃. Preferably, the heat treatment time is 0.5h-1.5h.
Citation Information
Cited By
Gradient functional high silicon steel soft magnetic composite iron core and preparation method and application thereof
CN121862555A